(untitled) (International conference on multidisciplinary science, 2023)
The article deals with the linguistic research of Uzbek construction terms and the history of the emergence of an explanatory dictionary of Uzbek architectural-construction terms and the theoretical issues of its creation. Methodological conclusions are given about the tasks, problems and their solutions, the relevance of creating a dictionary of construction-architecture terms. Focusing on the description of the works carried out in Uzbek and Russian linguistics in this field, the scope of these works is evaluated